The Role of Organizational Culture on Employee Performance Influenced by Job Satisfaction and Knowledge Sharing and Its Impact on Organizational Performance - Dibyo Yaksaprawira; Justine Tanuwijaya; Andreas Wahyu Gunawan (Universitas KH. Abdul Chalim Mojokerto, 2024)
This study aims to analyze the influence of Organizational Culture on Employee Performance through Job Satisfaction and Knowledge Sharing, and its impact on Organizational Performance. Based on the results of the study, it can be concluded that: (1) Organizational Culture has a positive effect on Employee Performance, which shows that employee perceptions of organizational culture in Digital Banks in Indonesia throughout Indonesia affect their performance. (2) Organizational Culture also has a positive effect on Knowledge Sharing, indicating that a high organizational culture affects the sharing of knowledge among employees. (3) Organizational Culture has a positive effect on Job Satisfaction, indicating that the perception of a good organizational culture increases employee job satisfaction. (4) Job Satisfaction has a positive effect on Employee Performance, so that high job satisfaction increases employee performance. (5) Knowledge Sharing has a positive effect on Employee Performance, indicating that high knowledge sharing contributes to employee performance. (6) Job Satisfaction fully and significantly mediates the relationship between Organizational Culture and Employee Performance, which means that job satisfaction is the main link between organizational culture and employee performance. (7) Knowledge sharing also fully and significantly mediates the relationship between Organizational Culture and Employee Performance, confirming that knowledge sharing plays an important role in the influence of organizational culture on performance. (8) Employee Performance has a positive effect on Organizational Performance, indicating that good employee performance contributes to overall organizational performance.